Wellness as a Mitigating Factor for Teacher Burnout. Issue 3 (October 2019) - Brasfield, Michelle Welch; Lancaster, Chloe; Xu, Y. Jade
Teacher stress and burnout have been associated with professional dissatisfaction and elevated rates of attrition. Knowledge has emerged to indicate that wellness may relieve professional stress that can precede burnout and departure from the profession; however, more research is needed to substantiate this relationship. The current study examined the potentially militating function of wellness in lowering burnout. For this study, 107 PreK-12th grade teachers completed the Maslach Burnout Inventory–Educator Survey and the Five-Factor Wellness Inventory. Results indicate significant relationships between reported burnout with wellness indicators and attrition. Implications for teachers, teacher education programs, and educational leadership teams are discussed.